PENGARUH DESENTRALISASI, PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA MANAJERIAL SKPD KOTA PEKANBARU - Hidrayadi, Rizon; -, Andreas; Savitri, Enni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of Decentralization, Participation Budget, Organization’s Commitment, and Work Motivation On The Performance Of Managerial SKPD’s Of Pekanbaru City Government. This study was conducted at SKPD of Pekanbaru City. The population in this study were employed who worked in the SKPD Pekanbaru City (26 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD, the secretary of SKPD, and the head of financial. The sample used in this study were 78 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0. The result of this study indicated that the Decentralization, Participation Budget, Organization’s Commitment and Work Motivation has significantly effect on effectiveness of the Performance Managerial. The magnitude of the effect (R2) the Decentralization, Participation Budget, Organization’s Commitmen, and Work Motivation on the effectiveness of the Performance Manajerial area was 47%. While the remaining 53% is influenced by other independent variabel that are not observed in this study.Keywords: Decentralization, Participation Budget, Organization’s Commitment, Work Motivation, Performance Managerial.